Histone deacetylase inhibitor‐mediated cell death is distinct from its global effect on chromatin. Issue 8 (28th May 2014) - Luchenko, Victoria L.; Litman, Thomas; Chakraborty, Arup R.; Heffner, Aaron; Devor, Christopher; Wilkerson, Julia; Stein, Wilfred; Robey, Robert W.; Bangiolo, Lois; Levens, David; Bates, Susan E.
Abstract : Romidepsin and vorinostat are histone deacetylase inhibitors (HDACis) that have activity in T‐cell lymphomas, but have not gained traction in solid tumors. To gain deeper insight into mechanisms of HDACi efficacy, we systematically surveyed 19 cell lines with different molecular phenotypes, comparing romidepsin and vorinostat at equipotent doses. Acetylation at H3K9 and H4K8 along with 22 other histone lysine acetylation and methylation modifications were measured by reverse phase proteomics array (RPPA), and compared with growth inhibition (IC50), and cell cycle arrest. These assays typically used to assess HDACi effect showed that acetylation and methylation of specific lysine residues in response to HDACis were consistent across cell lines, and not related to drug sensitivity. Using a treatment duration more reflective of the clinical exposure, cell death detected by annexin staining following a 6 h drug exposure identified a subset of cell lines, including the T‐cell lymphoma line, that was markedly more sensitive to HDAC inhibition. Kinetic parameters (Km values) were determined for lysine acetylation and for cell cycle data and were themselves correlated following HDACi exposure, but neither parameter correlated with cell death. The impact on cell survival signaling varied with the molecular phenotype. This study suggests that cellular response to HDACis can be viewed as two distinct effects: a chromatin effect and a cell death effect. All cells undergo acetylation, which is necessary but not sufficient for cell death. Cells not primed for apoptosis will not respond with cell death to the impact of altered histone acetylation. The divergent apoptotic responses observed reflect the variable clinical outcome of HDACi treatment. These observations should change our approach to the development of therapeutic strategies that exploit the dual activities of HDACis. Highlights: HDIs cause two distinct effects: a chromatin effect and a cell death effect. Acetylation after HDI is monotonous, found at multiple lysine residues. The impact on chromatin triggers apoptosis in only selected cell types. Short drug exposure models the divergent clinical responses. Further clinical development should take into account this differential effect.